Cytochrome P450 Monooxygenase CYP716A141 is a Unique β-Amyrin C-16β Oxidase Involved in Triterpenoid Saponin Biosynthesis in Platycodon grandiflorus. (23rd March 2017) - Tamura, Keita; Teranishi, Yuga; Ueda, Shinya; Suzuki, Hideyuki; Kawano, Noriaki; Yoshimatsu, Kayo; Saito, Kazuki; Kawahara, Nobuo; Muranaka, Toshiya; Seki, Hikaru
Abstract : The roots of Platycodon grandiflorus are widely used as a crude drug. The active components include a variety of triterpenoid saponins. Recent studies have revealed that Cyt P450 monooxygenases (P450s) function as triterpene oxidases in triterpenoid saponin biosynthesis in many plant species. However, there have been no reports regarding triterpene oxidases in P. grandiflorus. In this study, we performed transcriptome analysis of three different P. grandiflorus tissues (roots, leaves and petals) using RNA sequencing (RNA-Seq) technology. We cloned six P450 genes that were highly expressed in roots, and classified them as belonging to the CYP716A, CYP716D and CYP72A subfamilies. We heterologously expressed these P450s in an engineered yeast strain that produces β-amyrin, one of the most common triterpenes in plants. Two of the CYP716A subfamily P450s catalyzed oxidation reactions of the β-amyrin skeleton. One of these P450s, CYP716A140v2, catalyzed a three-step oxidation reaction at C-28 on β-amyrin to produce oleanolic acid, a reaction performed by CYP716A subfamily P450s in a variety of plant species. The other P450, CYP716A141, catalyzed the hydroxylation of β-amyrin at C-16β. This reaction is unique among triterpene oxidases isolated to date. These results enhance our knowledge of functional variation among CYP716A subfamily enzymes involved in triterpenoid biosynthesis, and provide novel molecular tools for use in synthetic biology to produce triterpenoid saponins with pre-defined structures.